Success Rate And Survival Of Resin-Bonded Fixed Dental Prostheses In The Anterior Region: A Literature Review - Galang Eka Nusa Wibowo; Owin Bambang (International Journal of Health Engineering and Technology, 2026)
Loss of anterior teeth may affect mastication, phonetics, esthetics, and the patient’s quality of life, thereby requiring appropriate rehabilitation. One of the treatment options widely used is resin-bonded fixed dental prosthesis (RBFDP) due to its minimally invasive and conservative nature, as well as its favorable esthetic outcomes. This literature review aims to evaluate the success and survival rates of RBFDPs in the anterior region based on recent scientific publications. This study employed a qualitative descriptive approach through literature searches in PubMed, Google Scholar, ScienceDirect, and Wiley Online Library databases using articles published between 2020 and 2026. Article selection was carried out based on predetermined inclusion and exclusion criteria, and the data were analyzed descriptively. RBFDPs demonstrate high success and survival rates in the anterior region, particularly in ceramic-based restorations and cantilever designs. Factors influencing success include the type of material, retainer design, quality of adhesion, occlusal conditions, patient oral hygiene, and the clinical techniques applied. The most commonly reported complications are debonding and retainer fracture. RBFDPs represent an effective and conservative rehabilitation option capable of providing favorable long-term functional and esthetic outcomes in cases of anterior tooth loss.